Kontakty św. Paulina z Noli z Rzymem i jego biskupami - Kasprzak, Dariusz (Vox Patrum, 2004)
The article aims to reconstruct on the basis of the writings of St. Paulinus of Nola both the way the famous master of Nola saw Rome and the significance of his pilgrimages there. Ancient, pre-Christian Rome is called by him the daughter of Babylon because of the pagan character of Rome and the numerous sins committed by its citizens as well. However, thanks to the presence of true believers such as Melanie or the relics of holy Apostles and martyrs like Peter and Paul, Pagan Rome becomes more the daughter of Zion and new Jerusalem. Paulinus of Nola and Terasia, his wife, once a year traveled to their monastery in Campania, from the grave of the martyr St. Felix to Rome, on the festival of the Apostles Peter and Paul, where they usually spent 10 days. Later, as bishop of Nola, he set off to Rome earlier, just after Easter. His pilgrimage usually lasted four weeks. Besides the religious aspect of traveling to Rome, the meetings with numerous Christian celebrities Corning to the festival of the Apostles in Rome were the goal of his pilgrimage. Since the very beginning Paulinus treated his journeys as a way to establish contacts with important priests of Christian Rome. For Paulinus these meetings gave him the opportunity to propagate the monastic style of life, which he himself adopted while still in Spain.